Peran Perempuan Dalam Gereja Katolik Menurut Dokumen Mulieris Dignitatem - gurusinga, rikha emyya (Pastoralia Jurnal Penelitian Dosen, 2025)
This study explores the role of women in the Catholic Church based on the apostolic letter Mulieris Dignitatem by Pope John Paul II. The research is rooted in the historical and social developments that have shaped women's position within the Church. Its objective is to identify and understand the Church’s theological perspective on women’s dignity, vocation, and contribution within family, society, and the Body of Christ. The method employed is a literature review, analyzing Church documents, theological literature, and relevant academic articles. The findings reveal that women possess equal dignity to men and have an irreplaceable role, particularly through their maternal qualities, sensitivity, and active participation in Church life. Nevertheless, structural limitations still hinder women from holding ecclesiastical leadership roles. The study concludes by emphasizing the need for further reflection and more inclusive implementation of Mulieris Dignitatem to strengthen the role of women in the modern Catholic Church.